A commentary on the Song of Solomon - Burrowes, George, 1811-date of death unknown (UK Banner of Truth, 1861)
Includes bibliogaphical references.
Reprinted 1958, 1960. First edition published 1853.
Keywords: Bible. O.T. Song of Solomon -- commentaries